Biochar of coal reject waste from coal mines, and its combination with chicken manure as an ameliorant material to increase rice paddy productivity - Sulistiono, Muhammad Ramadhan Fauzi; Hartono, Arief; Pulunggono, Heru Bagus (Brawijaya University, 2026)
Increasing coal production each year has led to more coal rejects, which become mining waste and are generally unused, potentially causing long-term environmental problems. Research on its use as a soil conditioner is still limited, and no studies have specifically developed pyrolysis coal rejects into biochar combined with chicken manure to increase rice productivity. This study aimed to elucidate the effects of applying coal reject biochar and chicken manure on rice growth and production, as well as on soil chemical properties in Karawang Regency. This study compared coal reject and chicken manure (RCCM) with coal reject biochar and chicken manure (RCBCM) at doses of 0 (control), 5, 10, 20, and 40 t ha-1 using a split-plot design. The results showed an increase in pH and organic C with increasing dose. The RCBCM plot had a higher organic C value than the RCCM. In addition, RCBCM produced 3.97 kg of harvested dry paddy per plot, respectively, which was higher than RCCM 3.51 kg. On a hectare scale, RCBCM produced 6.35 t ha?¹ of harvested dry paddy, while RCCM produced 5.617 t ha?¹, respectively. The 20 t ha?¹ dose produced 3.78 kg of harvested dry paddy per plot or 6.06 t ha?¹. This was not significantly different from that of a 40 t ha?¹ dose, which produced 4.96 kg per plot or 7.93 t ha?¹. Therefore, the 20 t ha-1 dose was recommended as the optimal dose.